Developing a Leadership Capability for Team Leaders in the Construction Industry: A Concept for Organizational Success - Wan Muda, Wan Hanim Nadrah; Libunao, Wilfredo Herrera; Mohd Salleh, Kahirol; Sulaiman, & Norlisa (Journal of Technical Education and Training, 2016)
Capable leaders are essential to unlock the potential of workforce, in terms of productivity, learning, continuous improvement, quality and customer service. This study was conducted to ascertain the Malaysian construction industry leaders’ conception of leadership capability. One of the mandates of Malaysia’s Construction Industry Development Board (CIDB) is to serve as a gateway for construction industry players to get involved in the international construction ventures, with the aim of enabling them to hold leadership positions in the future; as well as maintaining an open exchange of information with construction leaders worldwide. However, for a better understanding of leadership concepts and leadership skills, construction industry in Malaysia must unleash its potential as a source of wealth creation and provide opportunity for the betterment of quality of life. In ensuring the quality of workmanship at construction sites, leadership skills especially supervisory skill for site supervisors need to be enhanced. Undoubtedly, the role of research in determining the specific leadership skills and the needed core capabilities cannot be over-emphasized. In this study, qualitative research design with in-depth interview was used to collect the data and purposeful sampling was employed in selecting 15 research participants involving team leaders and human resource managers. The data was analyzed using thematic analysis with the aid of NVivo. Effective leadership has been found to be vital element in construction industry. The opinions from the respondents also indicate that they have knowledge on leadership and they had to enhance themselves with the elements in the concept to enable them to become better and more competitive leaders. Leaders in construction industry have a broad knowledge in technical skills conversely have fewer non-technical skills especially in leadership.